Hepatitis C in Israeli prisons: status report - Niv Michaeli; Anat Litvin; Nadav Davidovitch (BMC, 2020)
Abstract The article discusses and analyzes the changes that have taken place since 2016 in Israeli policy with regard to the treatment, diagnosis and detection of hepatitis C (HCV) in prison settings. The article finds indications of promising changes to official procedure, such as the statement by authorities that they plan to begin screening new inmates for HCV, and the increase in the number of inmates provided antiviral drugs. These measures, however, only came about after a prolonged campaign and legal battle by human rights organizations, patient advocacy groups and the medical community. Despite these encouraging changes, it appears that a significant portion of inmates in need of treatment are still not getting it due both to bureaucratic delays and to inmates' reluctance. In addition, in the absence of a suitable screening program, the extant figures of morbidity-high in themselves-may reflect underdiagnosis. The flaws in the policymaking process and in its implementation may be attributed, at least in part, to the fact that the prison healthcare system is under the aegis of the Israel Prison Service and not that of a medical body. This reality places the medical staff in prisons in a state of dual loyalty, and also means the prison healthcare system is excluded from national health plans and major sources of budgeting, leaving it without sufficient means to provide the necessary level of care. These problems plague the prison healthcare system in general and are not limited to its handling of HCV. These challenges are not unique to Israel, and many other Western countries must also face the obstacles that are the result of prison healthcare services being subject to the authority of the correctional establishment. As this test case demonstrates, extended active involvement by civil organizations and the medical community are essential to promoting and ensuring inmates' right to health.